Finding God among our neighbors : an interfaith systematic theology - Largen, Kristin Johnston, 1968- (Minneapolis : : Fortress Press, 2013)
"Students of theology live in a world defined by interreligious dialogue. This supplemental theology text prepares students for the real task of understanding and articulating their Christian beliefs in a religiously and culturally diverse world. Concentrating on the anchoring subjects of God, creation, and humanity, she explores these loci in the broader context of interreligious dialogue with Hinduism, Judaism, Buddhism, and Islam to better understand the Christian tradition"-- Publisher.
Part I. Introductions to world religions. A brief introduction to Hinduism -- A brief introduction to Judaism -- A brief introduction to Buddhism -- A brief introduction to Islam -- Part II. A comparative approach to Christian theology. God-talk -- Human being, being human -- A wild and wonderful world
Keywords: Theology, Doctrinal--21st century; Christianity and other religions--Hinduism.; Christianity and other religions--Judaism.; Christianity and other religions--Buddhism.